France : Financial Sector Assessment Program-Technical Note-Balance Sheet Risks and Financial Stability. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note on balance sheet risks and financial stability on France discusses that macroprudential policy setting faces the challenge of identifying growth of financial and macroeconomic variables above and below potential. A macro-financial structural model is presented that captures: sectoral dynamics of firms and banks and feedbacks between them; capital and default risk dynamics of each sector; capital and risk gaps id est, deviations of capital and default risk from potential, and it provides; and a quantitative method for measurement. The report finds that default risk fluctuates during time between being too high and too low. Risk is too high during four episodes: prior to the Technology Crisis, prior to the Global Financial Crisis, prior to the Sovereign Debt Crisis, and now. The analysis implies that firms should be encouraged to strengthen their equity capital base by retaining earnings or issuing equity. This could be done also indirectly by publishing related research.